Peran Guru Dalam Membangun Kesadaran Kewarganegaraan Melalui Pelajaran Pendidikan Pancasila Dan Kewarganegaraan Siswa Kelas XI SMA Swasta Katolik Mariana Medan - Manik, Selly Lorenza; Pasaribu, Kondios Meidarlin; Simanjuntak, Hotmaida (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the role of teachers in building citizenship awareness through Pancasila and Citizenship Education (PPKn) lessons for 11th grade students of SMA Swasta Katolik Mariana. Citizenship awareness is very important in shaping the character of the nation, and the role of teachers as educators is very important in this process. This type of research uses a qualitative method with data collection techniques through interviews, observations, and documentation. of PKn teachers with 11th grade students. Data analysis was carried out using data reduction techniques, data presentation, and drawing conclusions. The results of the study showed that teachers play an important role in building students' citizenship awareness by linking PPKn material to everyday life and relevant social problems. Teachers also involve students in various activities that support understanding of the rights and obligations of citizens. In addition, the approach used in learning contributes to the development of students' positive attitudes towards Pancasila and citizenship values. This study confirms that the active role of teachers is very important in creating a deep understanding of students' civic awareness which can increase students' awareness of the importance of actively participating in national and state life.